Nutritional approach to failure to thrive - Su Jin Jeong (Korean Pediatric Society, 2011)
Failure to thrive (FTT) is a term generally used to describe an infant or child whose current weight or rate of weight gains is significantly below that expected of similar children of the same age, sex and ethnicity. It usually describes infants in whom linear growth and head circumference are either not affected, or are affected to a lesser degree than weight. FTT is a common problem, usually recognized within the first 1-2 years of life, but may present at any time in childhood. Most cases of failure to thrive involve inadequate caloric intake caused by behavioral or psychosocial issues. The most important part of the outpatient evaluation is obtaining an accurate account of a child's eating habits and caloric intake. Routine laboratory testing rarely identifies a cause and is not generally recommended. FTT, its evaluation, and its therapeutic interventions are best approached by a multi-disciplinary team includes a nutritionist, a physical therapist, a psychologist and a gastroenterologist. Long term sequelae involving all areas of growth, behavior and development may be seen in children suffering from FTT. Early detection and early intervention by a multi-disciplinary team will minimize its long term disadvantage. Appropriate nutritional counseling and anticipatory guidance at each well child visit may help prevent some cause of FTT.